2021
DOI: 10.3389/fmicb.2021.589487
|View full text |Cite
|
Sign up to set email alerts
|

Student Outcomes From a Large-Enrollment Introductory Course-Based Undergraduate Research Experience on Soil Microbiomes

Abstract: In recent years, national reports have called for undergraduate laboratory education that engages students in authentic research experiences. As a result, a number of course-based undergraduate research experiences (CUREs) have been developed in biological sciences and some specifically in microbiology. Students benefit from CUREs much like in traditional mentored research experiences, where students carry out independent projects in faculty laboratories. These benefits include increased self-efficacy in resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Mateo specifically indicated that the context itself as motivating, and others noted endemic feedback, as when Emma’s model was “super weird,” when Dinesh’s experiment was not “going right” or, as Sophia suggested, that the published research could offer insight about the choices they should make. This finding extends past research showing that the context of CUREs can support student sense-making, ,, suggesting context might operate in more complex ways. In these expressions, students attributed agency to the context, displayed as consistent use of third-person subjects (e.g., “the model,” “it”).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Mateo specifically indicated that the context itself as motivating, and others noted endemic feedback, as when Emma’s model was “super weird,” when Dinesh’s experiment was not “going right” or, as Sophia suggested, that the published research could offer insight about the choices they should make. This finding extends past research showing that the context of CUREs can support student sense-making, ,, suggesting context might operate in more complex ways. In these expressions, students attributed agency to the context, displayed as consistent use of third-person subjects (e.g., “the model,” “it”).…”
Section: Resultssupporting
confidence: 87%
“…A direct relationship between students and their chosen fields has been found to foster excitement and a sense of ownership that translates to persistence in science, both in chemistry and chemical engineering. , Sometimes, CUREs are designed and implemented as a replacement for lectures . However, most CUREs are set in laboratory courses, providing students with opportunities to design experiments. , While many CUREs are set in upper-division courses, this is not always the case, with some implemented in general chemistry. , These hands-on authentic experiences give students a glimpse into what being a professional in their field might be like, while supporting increased science self-efficacy, including skills beyond using basic equipment . By authentic, we mean that the problems tackled have a “primary purpose and source [that is] a need, a practice, a task, a quest and a thirst existing in a context outside of schooling.”…”
Section: Introductionmentioning
confidence: 99%
“…While there are no universal guidelines for interpreting Cronbach's alpha values, these values fall within the good to excellent range of reliability (Taber, 2018). Analogous modifications were previously determined to retain high internal consistency and reliability (Lo & Le, 2021;Mordacq et al, 2017). Students also indicated their intentions to continue their scientific training through coursework, laboratory experiences, and career pathways using previously developed items (Lo et al, 2014).…”
Section: Quantitative Instruments and Analysismentioning
confidence: 99%
“…Among them, what kind of teaching method should be adopted to meet the needs of undergraduate vocational education to cultivate high-quality technical talents is the first issue to be considered. Whether from the objective needs of economic and social development or from the internal requirements of vocational education to achieve high-quality development, it is urgent to explore undergraduate vocational education [5]. However, in the current practice of vocational education reform, China still lacks in-depth theoretical research and practical exploration on how to build vocational education at undergraduate level.…”
Section: Introductionmentioning
confidence: 99%